Spontaneous disappearance of common bile duct stones following the insertion of a new dumbbell‐shaped, covered self‐expandable metallic stent in a patient with benign biliary stricture. Issue 5 (4th May 2021) - Ishizaki, Yuto; Sugimoto, Mitsuru; Takagi, Tadayuki; Suzuki, Rei; Konno, Naoki; Asama, Hiroyuki; Sato, Yuki; Irie, Hiroki; Okubo, Yoshinori; Nakamura, Jun; Takasumi, Mika; Hashimoto, Minami; et al.
Abstract: The new dumbbell‐shaped, covered self‐expanding metallic stent can efficiently remove the choledocholiths in cases with common bile duct (CBD) strictures; moreover, it may potentially prevent a positional displacement and contribute to the better improvement of the CBD stricture. Abstract : The new dumbbell‐shaped, covered self‐expanding metallic stent can efficiently remove the choledocholiths in cases with common bile duct (CBD) strictures; moreover, it may potentially prevent a positional displacement and contribute to the better improvement of the CBD stricture.